2022
DOI: 10.1089/bfm.2021.0346
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Pregnancy-Related Anxiety Reduces Breastfeeding Exclusiveness and Duration: A Prospective Cohort Study

Abstract: Objective: Most research has focused on the role of prenatal mental health difficulties on breastfeeding practices, whereas pregnancy-related anxiety (PrA) has been less studied, despite its high prevalence. Identifying new vulnerable subgroups in which the breastfeeding rate remains low is important for health care workers to implement targeted interventions. This study is aimed to explore the association between PrA and breastfeeding practices. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
1
2
0
1
Order By: Relevance
“…We add to the literature [39] by showing similar findings in pregnancy-related anxiety, a special mode of prenatal stress that has received little attention but predicts fetal development outcomes more accurately than general anxiety and depression symptoms [40,41]. Compared with our two previous works [7,8], the present study found similar gender-dependent outcomes but only focused on pregnancy-related anxiety at the third trimester because this cohort data showed that the third trimester is the critical period of pregnancy-related anxiety on child neurobehavioral development [42]. All the three works [7,8] reported the male-bias hyperactivity symptoms but only two works [8] reported the femalebias emotional symptoms.…”
Section: Discussionsupporting
confidence: 76%
“…We add to the literature [39] by showing similar findings in pregnancy-related anxiety, a special mode of prenatal stress that has received little attention but predicts fetal development outcomes more accurately than general anxiety and depression symptoms [40,41]. Compared with our two previous works [7,8], the present study found similar gender-dependent outcomes but only focused on pregnancy-related anxiety at the third trimester because this cohort data showed that the third trimester is the critical period of pregnancy-related anxiety on child neurobehavioral development [42]. All the three works [7,8] reported the male-bias hyperactivity symptoms but only two works [8] reported the femalebias emotional symptoms.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, higher levels of depressive and anxiety symptoms in mothers who are not breastfeeding have been reported, 63,64 whereby using baby formula milk may be a predictor of these symptoms. Interestingly, we observed that living near to chemistry laboratory or factory did not increase the risk for MIH, and a possible explanation is that in the locality there are very few and usually small factories or laboratories, which may not produce a large amount of waste reducing their pollution.…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, studies conducted prior to the pandemic have established links between perinatal distress and poorer child outcomes including worse cognitive performance (Glover, 2015), psychiatric disorders (Bale et al, 2010;Van den Bergh et al, 2020), and more socioemotional (Porter et al, 2019) and behavioral (Kingston & Tough, 2014) problems. Pregnancy-related anxiety (i.e., speci c anxiety about the emotions, thoughts, and physical symptoms experienced by pregnant individuals; Bayrampour et al, 2016), has also been uniquely linked to negative developmental outcomes in offspring, including developmental delays (Shao et al, 2021) and risk for emotional and behavioral problems (Wang et al, 2021). Thus, heightened prenatal pandemic-related anxiety may also signal risk for poorer developmental outcomes in children, although studies have yet to examine such associations within a prospective framework.…”
Section: Introductionmentioning
confidence: 99%